2005
DOI: 10.4103/0972-5229.19766
|View full text |Cite
|
Sign up to set email alerts
|

Severe lung injury following inhalation of nitric acid fumes

Abstract: Objective: We present a rare case of survival following inhalation of nitric acid fumes and its decomposi tion products, which resulted in severe pulmonary edema and Acute Respiratory Distress Syndrome (ARDS). Successful outcome followed ventilatory support and use of steroids. Design: Case report. Setting: Terti ary-level medical intensive care unit. Patient: A single case of inhalation of nitric oxide fumes. Interven tion: Ventilatory support and addition of steroids. Measurement and main results: Improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Toxic exposure to nitrogen dioxide has generally occurred in four circumstances: Exposure to silo gases, welding, combustion of nitrogen-containing materials, and spills of nitric acid. [ 1 ]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Toxic exposure to nitrogen dioxide has generally occurred in four circumstances: Exposure to silo gases, welding, combustion of nitrogen-containing materials, and spills of nitric acid. [ 1 ]…”
Section: Discussionmentioning
confidence: 99%
“…This delayed effect has been well described in almost all cases of nitric acid and nitrogen dioxide inhalation injury reports. [ 1 ] Hajela et al, have reported three deaths owing to rapidly progressing pulmonary edema of delayed onset after inhalation of fumes due to accidental nitric acid exposure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations